When political candidates "go positive": the effects of flattering the rival in political communication. (2nd July 2016) - Cavazza, Nicoletta
Abstract: In the field of political communication, the effects of negative propaganda strategies have been long studied. In the current work, I investigated the perceived and actual persuasiveness of an unexplored positive propaganda strategy, i.e., addressing a flattery to the rival in a political speech. In a 2 × 2 full-factorial design experiment, a fictitious candidate (a man or a woman) flattered, or did not flatter, an opponent in a political speech. Results showed that when the candidate flattered a rival s/he influenced the likelihood of being voted through source trustworthiness evaluation, irrespective of the candidate's gender. Theoretical and practical implications are discussed.